Effect of reduced spray programmes on incidences of apple scab, powdery mildew and codling moth damage in environmentally freindly apple production systems - Holb, I. J.; Fazekas, M.; Abonyi, F.; Lakatos, P.; Thurzó, S.; Nyéki, J.; Szabó, Z.; Kruppa, J.; Balla, B. (International Journal of Horticultural Science, 2009)
Still a large amount of pesticides and spary applications are used in environmentally friendly fruit production systems; therefore, the aim of our study was first to test the in vitro effeicacy of some fungicides against a key apple disease (apple scab), and secondly to evaulate the effectiveness of reduced spray programmes against apple scab, powdery mildew and coding moth in integrated and organic apple orchards. In vitro efficacy of 7 fungicides (Champion 50 WP, Kocide 2000, Nordox 75 WG, Olajos rézkén, Kumulus S, Rézkén, Rézoxiklorid) and another 6 fungicides (Score 25 EC, Efuzin 500 SC, Systane, Folicur Solo, Zato Plusz, Rovral) approved in organic and integrated production systems, respectively, were tested against apple scab. Altogether four spray programmes were performed i) standard integrated: sprays followed by forecasting systems during the season, ii) reduced integrated: sprays followed by forecasting systems but only 75% of the spray numbers used during the season-long spray programme, iii) standard oragnic: sprays applied every 7–14 days during the season and iv) reduced organic: 60% of the spray numbers used during the season-long spray programme. In vitro results showed that fungicides (with active ingredients of copper and sulphur) applied in organic production showed relatively high percent growth capacity of the apple scab fungus. Rézkén showed the highest and Kumilus S the lowest efficacy against apple scab. Fungicides applied in integrated production showed relatively low percent growth capacity of the apple scab fungus. Score 25 EC showed the highest and Rovral the lowest efficacy against apple scab. Field study showed that reduced spray programmes did not increase significantly scab incidence in the integrated field. However, scab incidence increased significanly (above 30%) in the reduced spray programme for the organic orchard.Mildew incidence was low (below 5%) in both integrated and organic spray programmes. Mildew incidence on both shoots and fruits increased significanly in the reduced spray programme for the organic orchard. Incidence of codling moth damage was affected the most by standard vs. reduced spray programmes. Though incidence remained below 10% in the integrated plots, the incidence was significantly higher in the reduced spray programme compared to the standard programme. Similar results were obtained for organic spary programmes, but the incidence was 10 times higher and the differences among the two programmes were larger.,